THE PROS AND CONS OF A SIDE HUSTLE IN AN EMPLOYMENT RELATIONSHIP: Bakenrug Meat (Pty) Ltd t/a Joostenberg Meat v CCMA [2022] 4 BLLR 319 (LAC) - Clarence I Tshoose; Justice M Kgaphola (Obiter, 2023)
This case note centres on the duty of good faith, with a particular emphasis on moonlighting. Determination of the scope of the duty of good faith was the crux of the judgment of the Labour Appeal Court (LAC) in Bakenrug Meat t/a Joostenburg Meat v CCMA (2022 (4) BLLR 319 (LAC)) (Bakenrug). By inquiring into the “scope”, the case note highlights that the duty is wide and has numerous dimensions. Thus, lack of clarity and confusion by courts creates difficulties for the fairness or otherwise of dismissals for alleged moonlighting. Compounding this challenge, a recurring problem in labour relations involves the extent to which employers discipline employees for moonlighting (the practice of holding more than one job).After outlining the salient facts, the case note engages with the CCMA award, the decision of the Labour Court (LC) and the judgment of the LAC. The balance of analysis is structured in the following way. First, there is an evaluation of the concept of the “duty of good faith” in circumstances of moonlighting. Secondly, the case note unpacks the notion of “conflict of interest” in employment relations. Thirdly, misconduct as a ground that warrants dismissal is viewed in the context of moonlighting. Finally, the note makes some concluding remarks.